MicroRNA-375-3p Alleviates Salicylate-Induced Neuronal Injury by Targeting ELAVL4 in Tinnitus - Zhu, Jingjing; Chen, Zhen; Yu, Bo; Zhang, Lan; Ai, Fen (Journal of Neurological Surgery Part B: Skull Base, 2023)
Purpose Tinnitus is a phantom perception of sound in the absence of acoustic source. Previous evidence has indicated that miR-375-3p is downregulated in rats with tinnitus in comparison to the controls. Nevertheless, its molecular mechanism underlying tinnitus pathogenesis is unclarified.Methods SH-SY5Y cells were differentiated into neuronlike cells and stimulated with salicylate to mimic tinnitus in vitro. Immunofluorescence staining was utilized for measuring expression of NR2B (glutamate ionotropic receptor NMDA type subunit 2B). Intracellular reactive oxygen species (ROS) level was determined using DCFH-DA assay kit. Real-time quantitative polymerase chain reaction as well as western blotting was utilized for examining RNA and protein levels. Luciferase reporter assay was implemented for verifying the interaction between miR-375-3p and ELAVL4 (ELAV-like RNA-binding protein 4).Results Salicylate treatment enhanced levels of NR2B and the early immediate gene ARC as well as ROS production. miR-375-3p was downregulated in salicylate-treated group. Overexpressing miR-375-3p attenuated the effects induced by salicylate in SH-SY5Y cells. miR-375-3p targeted ELAVL4 and upregulating ELAVL4 reversed miR-375-3p upregulation–triggered effects on SH-SY5Y cells under salicylate treatment.Conclusion miR-375-3p mitigates salicylate-triggered neuronal injury in SH-SY5Y cells by regulating ELAVL4 expression.
Keywords: tinnitus; salicylate; miR-375-3p; neurons; ELAVL4